Limites e desafios da transição agroecológica: um estudo de caso na Cooperativa dos Produtos Orgânicos do Xingu em Brasil Novo - PA - ARAÚJO, Stéphanie Julianne Bilhar (2021)
Organic farming is an ecological production process aimed at producing healthy food, which has been gaining ground in the Transamazonico territory, shaped mainly by the conservationist thinking of family farmers, in search of a better quality of life, of the ecosystem equilibrium, of the conventional production, and the use of pesticides on properties. This work aimed to evaluate the agroecological transition process of the farmers associated with the Xingu Organic Products Cooperative - COOPOXIN, in the municipality of Brasil Novo - PA. The research was qualitative and sought to understand the transition processes, elements such as the contribution of the cooperative in relation to agroecological practices, the motivation of the interviewees in relation to organic production and the main obstacles to this production. The interviews were conducted using a semi-structured questionnaire with ten members and two members of the cooperative's board of directors. The results of the work demonstrated that organic agriculture in Brazil Novo is still in the process of being affirmed, with the main crop being the cocoa crop marketed by the cooperative and the main generator of agricultural income of the families. It was identified that the cooperative present difficulties in the accomplishment of agroecological practices in their properties, such as the fermentation of the almond, the composting and the fertilization of the cacao plantations. The families reported that the limitation in the accomplishment of the practices is related to the lack of labor and lack of materials needed to produce the inputs, also requiring actions conducted by the Cooperative. Based on the evaluations the research sought to contribute to the greater visibility of organic agriculture in the region and to serve as a basis for future research.